117k views
4 votes
I need a step by step of this equation please -2(3x+1)=26

1 Answer

3 votes

Answer:

x = -14/3

Explanation:

-2(3x + 1) = 26

Distribute the -2 to the number in the parentheses.

-6x - 2 = 26

Add 2 to both sides of the equation.

(-6x - 2) + 2 = 26 + 2

-6x = 28

Divide both sides of the equation by -6.

(-6x)/-6 = 28/-6

x = -28/6

x = -14/3

User Onexf
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.